Performance of hybrid AI2O3:SiO2 W:EG in PEM fuel cell distributor plate / Muhammad Syafiq Idris … [et al.] - Idris, Muhammad Syafiq; Zakaria, Irnie Azlin; Nazari, Putri Nur Afiqah; Wan Mohamed, Wan Ahmad Najmi; Wan Hamzah, Wan Azmi (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2023)
Efficient thermal management is essential for the optimal performance and durability of the Proton Exchange Membrane Fuel Cell (PEMFC). However, the conventional passive cooling methods require a larger heat exchanger for better heat dissipation. Alternatively, nanofluids as a coolant have gained attention recently due to their enhanced heat transfer properties. This investigation aims to evaluate the thermal performance of hybrid nanofluids in a distributor type of PEMFC cooling plate. In this investigation, 0.5% volume concentration of mono Al2O3, mono SiO2 nanofluids, and hybrid Al2O3:SiO2 nanofluids with a mixture ratio of 10:90, 30:70, 50:50, and 70:30 in 60:40 W:EG were investigated. The cooling plate was modelled and a fixed heat flux of 6500 w/m2 was applied to replicate the actual working parameter of PEMFC. The study shows that the heat transfer coefficient was improved by 61% in 10:90 hybrid nanofluids of Al2O3:SiO2 in W:EG in comparison to the base fluid. Meanwhile, the accompanied pressure drops in 10:90 hybrid nanofluids of Al2O3:SiO2 in W:EG show a reduction up to 4.38 times lower as compared to single Al2O3 nanofluids at Re 1800. This is advantageous since it will reduce the parasitic loss related to the PEM fuel cell.